On Initial Segments of Turing Degrees Containing Simple T-Mitotic but not wtt-Mitotic Sets - Mokatsian, Arsen H. (Mathematical Problems of Computer Science, 2021)
We consider the properties of computably enumerable (c.e.) Turing degrees containing sets, which possess the property of a T-mitotic splitting but don’t have a wtt-mitotic splitting. It is proved that for any noncomputable c.e. degree b there exists a degree a, such that a · b and a contains a simple T- itotic set, which is not wtt-mitotic.